2022
DOI: 10.1108/jcefts-09-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of women in the face of climate change: a study of Wayanad district of Kerala, India

Abstract: Purpose The relationship between women and extreme weather events is a significant issue given differential impact, adaptation strategies and coping mechanisms for genders. However, the women’s vulnerability and its determinants remain an understudied area. The paper aims to fill this important gap in literature by focusing on women’s vulnerability during the recent floods in the rural areas of Indian state of Kerala using primary data. With a focus on identifying the socioeconomic factors associated with wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…In a study in Kerala, India, women were shown to have greater vulnerability given floods, and that they may be assisted best by access to financial resources and information programs that are targeted to them. The frequency of extreme events due to climate change necessitates a shift of approach from relief and response to preparedness and availability of resources to reduce identified vulnerability [25]. Nyahunda and associates suggested that "vulnerabilities and inequalities manifest through lack of land and property rights, discrimination from decision-making processes, poverty and lack of adequate knowledge about climate change mitigation and adaptation," and that this was aggravated by a lack of social work involvement [26].…”
Section: Climate Change Impacts On Rural Areas: Extreme Events Source...mentioning
confidence: 99%
“…In a study in Kerala, India, women were shown to have greater vulnerability given floods, and that they may be assisted best by access to financial resources and information programs that are targeted to them. The frequency of extreme events due to climate change necessitates a shift of approach from relief and response to preparedness and availability of resources to reduce identified vulnerability [25]. Nyahunda and associates suggested that "vulnerabilities and inequalities manifest through lack of land and property rights, discrimination from decision-making processes, poverty and lack of adequate knowledge about climate change mitigation and adaptation," and that this was aggravated by a lack of social work involvement [26].…”
Section: Climate Change Impacts On Rural Areas: Extreme Events Source...mentioning
confidence: 99%
“…It comes more distinguished for marginal household conditions such as the characteristics of low-income people, less developed communities, very young and very old, women, persons with disabilities and health problems. These features determine the level of vulnerability and they will be more vulnerable in times of disasters [9].…”
Section: Introductionmentioning
confidence: 99%